2019
DOI: 10.1016/s2352-4642(18)30309-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of early diabetes-related complications in adolescents and young adults with type 1 diabetes: an observational cohort study

Abstract: Background. One in three adolescents and young adults with type 1 diabetes have at least one early diabetes-related complication/comorbidity. However, the prevalence, patterning, and risk factors for co-occurring complications in this population are not well understood. Methods. The SEARCH for Diabetes in Youth observational cohort study includes 1327 individuals diagnosed with type 1 diabetes before 20 years of age from 5 United States locations. Sociodemographic and metabolic risk factors were assessed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Adolescence is a high risk period for the development of complications of T1DM, as optimal glycaemic control is difficult to achieve, due to the effect of hormonal changes and psychosocial factors 13,14 . The first signs of vascular complications appear during adolescence and subclinical manifestations are common, however, hard endpoints, such as overt proteinuria, proliferative retinopathy or cardiovascular events are rare 15,16 . Subclinical manifestations include early increases in urinary albumin excretion, changes in the retinal microvasculature and subclinical changes in large blood vessels, including increased arterial stiffness, aortic intima-media thickness (aIMT) and carotid intima-media thickness (cIMT) 15 (Figure 1).…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…Adolescence is a high risk period for the development of complications of T1DM, as optimal glycaemic control is difficult to achieve, due to the effect of hormonal changes and psychosocial factors 13,14 . The first signs of vascular complications appear during adolescence and subclinical manifestations are common, however, hard endpoints, such as overt proteinuria, proliferative retinopathy or cardiovascular events are rare 15,16 . Subclinical manifestations include early increases in urinary albumin excretion, changes in the retinal microvasculature and subclinical changes in large blood vessels, including increased arterial stiffness, aortic intima-media thickness (aIMT) and carotid intima-media thickness (cIMT) 15 (Figure 1).…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…Young people with diabetes have high mortality due to acute metabolic complications (diabetic ketoacidosis, dead‐in‐bed syndrome), but also due to cardiovascular diseases leading to reduced life expectancy . In particular, those with diabetes onset below the age of 10 years seem to be vulnerable with a life expectancy almost 14–18 years shorter than that of their peers from the general population . Furthermore, a young child's cognitive development can be impaired by hyperglycaemia and diabetic ketoacidosis .…”
Section: Introductionmentioning
confidence: 99%
“…The SEARCH study has previously shown that the number of cardiovascular risk factors did not change significantly in participants with type 1 diabetes, but increased over time in participants with type 2 diabetes, a diabetic phenotype with a higher prevalence of obesity at diagnosis 34 . Early complications of diabetes co‐occurred in adolescents and young adults with diabetes, and included arterial stiffness and hypertension 35 . Youths and young adults with type 2 diabetes had a higher age‐adjusted prevalence of macrovascular outcomes such as arterial stiffness and hypertension than youths and young adults with type 1 diabetes 6 .…”
Section: Discussionmentioning
confidence: 99%